Successful treatment of esophagopleural fistula following pulmonary resection for primary lung cancer: a case report - Keisuke Eguchi; Masaharu Ogura; Kazuhiko Hisaoka; Emima Bekku; Shutaro Suda; Tatsuya Shimogawara; Yoshie Kadota; Shigeshi Ono; Fumitaka Asahara; Yutaka Takigawa; Noriaki Wada; Hirotoshi Hasegawa; et al. (Surgical Case Reports, 2019)
Abstract Background We report a rare case of esophagopleural fistula (EPF) developing during the postoperative period after pulmonary resection for primary lung cancer. Case presentation A 71-year-old male who underwent video-assisted thoracoscopic right lower lobectomy with lymph node dissection for primary lung cancer developed severe stabbing pain in his right shoulder and high fever 3 days after the operation. The fever persisted, the cough became more productive, and a plain chest X-ray showed slight a few infiltrative opacities in the right lung field. Intravenous antibiotic therapy was initiated. The patient developed a right pneumothorax 5 days after the operation, and contaminated discharge from the right chest tube was noted. A chest computed tomography showed right-sided empyema, while bronchoscopic examination revealed no evidence of a bronchopleural fistula. Open-window thoracostomy (OWT) was performed. Finally, 2 days after the OWT, the patient was diagnosed as having an EPF, because the right chest cavity was found to be contaminated with food materials. Ample purification of the right chest cavity was achieved by repeated dressing changes, and the EPF was finally closed by omentopexy. The post-surgical course was uneventful. Five weeks after the omentopexy, an esophagogram revealed no leakage of the contrast medium from the esophageal wall. The patient was discharged 13 weeks after the omentopexy. Conclusion While EPF following pulmonary resection is a rare complication, it can lead to critical situations and the diagnosis is difficult. Prompt OWT and omentopexy were found to be effective treatment procedures for EPF following lung surgery.